Impact of cattle slurry application methods on ammonia losses and grassland nitrogen use efficiency. (15th December 2022) - Nyameasem, John Kormla; Zutz, Mareike; Kluß, Christof; Huf, Martin ten; Essich, Christoph; Buchen-Tschiskale, Caroline; Ruser, Reiner; Flessa, Heinz; Olfs, Hans-Werner; Taube, Friedhelm; Reinsch, Thorsten
Abstract: Optimal manure management is required to ensure efficient nutrient supply to farmland and to avoid adverse environmental impacts. Accordingly, ammonia (NH3 ) emissions associated with different slurry application techniques were investigated in grassland trials under different soil and weather conditions across Germany. Cattle slurry was applied in two dressings, early in spring and after the first silage cut, with a target amount of 170 kg N ha −1 . The application treatments comprised: trailing shoe (TS), acidified slurry applied with trailing shoe (TS + A), open slot injection (SI), and slurry treated with a nitrification inhibitor (NI) applied by slot injection (SI + NI). In addition, slurry application techniques were compared with a non-N-fertilized control and a mineral fertilizer treatment (calcium ammonium nitrate, CAN). NH3 measurements followed each N application event. NH3 losses were equivalent to 1–39% of total ammoniacal nitrogen (TAN) applied. The average NH3 mitigation potential of the different slurry application techniques compared to TS was 45.7 ± 7, 21.2 ± 6.2 and 13.7 ± 8.2% for TS + A, SI and SI + NI, respectively. The use of nitrification inhibitor with slot injected slurry did not increase NH3 losses relative to TS ( p > 0.05). Mean apparent N use efficiency was two times higher for CAN (49%) than the slurry treatments (24%) but was comparable between SI + NI and CAN in five out of the eight cases. Our results indicate that mean TAN related NH3 emissions of tested treatments (3.3, 22.6, 12.2, 17.8 and 19.3% for CAN, TS, TS + A, SI and SI + NI, respectively) were generally lower than described in previous studies. Moreover, the results suggested possible increases in NH3 mitigation and N use efficiency when cattle slurry is applied with acidification or injection techniques. We found no evidence that NI addition to slot injected slurry, a treatment discussed as a measure to reduce N2 O emission and nitrate leaching, changed NH3 emission. Graphical abstract: Image 1 Highlights: Optimal manure management avoids adverse environmental impacts on grassland. Consistent data needed to quantify and evaluate site effects on NH3 emission. NH3 losses from cattle slurry represent 12–23% of ammoniacal nitrogen applied. NH3 losses depended on the application technique, site or experimental year. Slurry acidification showed the highest NH3 reduction potential.